Osteomyelitis and Osteonecrosis in Inflammatory Bowel Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Osteomyelitis and osteonecrosis are skeletal disorders seen in patients with inflammatory bowel disease (IBD). Osteomyelitis usually occurs in the pelvic bones, especially in complicated Crohn's disease, presumably by direct extension from a pelvic inflammatory mass, abscess or fistulous tract. Diagnosis of osteomyelitis may be difficult and can lead to spinal extension of the septic process with a resultant neurological deficit, including paraplegia. Osteonecrosis or avascular necrosis has been reported in patients with either ulcerative colitis or Crohn's disease, often, but not exclusively, during or following steroid treatment. The disease is often multifocal, but its natural history is unknown, especially if diagnosed early with modern imaging methods, such as magnetic resonance. In IBD patients, the relationship between osteonecrosis and steroid use is unknown. An adverse steroid effect on bones, especially the femoral heads, may develop in some patients with IBD but, to date, this hypothesis remains unproven. Critical evaluation of published data reveals no consistent association between osteonecrosis and steroid treatment in IBD patients.